The Costs of Power Interruptions in Germany - an Assessment in the Light of the Energiewende - Christian Growitsch; Raimund Malischek; Sebastian Nick; Heike Wetzel (Institute of Energy Economics at the University of Cologne (EWI), 2013)
The German Energiewende's potential effects on the reliability of electricity supply as well as the corresponding economic consequences have recently entered both the political and scientific debate. However, empirical evidence of power outage costs in Germany is rather scarce. Following a macroeconomic approach, we analyse the economic costs imposed by potential power interruptions in Germany. Investigating a rich data set on industry and households we estimate both Values of Lost Load (VoLLs) and associated costs of power interruptions for different German regions and sectors and every hour of the year. This disaggregated approach allows for conclusions for optimal load shedding in case of technical necessity and the economic efficiency of measures to improve security of supply. We find that interruption costs vary significantly over time, between sectors and regions. Peaking on midday of a Monday in December at 750 Mioe per hour, the average of total national outage costs amount to approximately 430 Mioe per hour. Our results emphasize the prominent regional aspect of the German Energiewende as the regions with the highest estimated cost of interruptions in South and West Germany coincide with the areas which face nuclear power plant shut downs in the near future.
Keywords: D61; L94; Q40; Q41; 330; Security of Supply; Value of Lost Load (VoLL); German Energiewende; Electricity outage costs